The Oxford handbook of citizenship - Shachar, Ayelet, 1966-; e; Bloemraad, Irene, 1972-; Vink, Maarten Peter, 1975- (Oxford : Oxford University Press, 2017)
Contrary to predictions that it would become increasingly redundant in a globalising world, citizenship is back with a vengeance. 'The Oxford Handbook of Citizenship' brings together leading experts in law, philosophy, political science, economics, sociology, and geography to provide a multidisciplinary, comparative discussion of different dimensions of citizenship: as legal status and political membership; as rights and obligations; as identity and belonging; as civic virtues and practices of engagement; and as a discourse of political and social equality or responsibility for a common good. The contributors engage with some of the oldest normative and substantive quandaries in the literature, dilemmas that have renewed salience in today's political climate.
Revisiting the Classical Ideal of Citizenship / Ryan Balot -- Comparing Citizenship Regimes / Maarten Vink -- Citizenship and Human Rights / David Owen -- Citizenship and Cultural Diversity / Daniel Weinstock -- Citizenship and the Franchise / Jo Shaw -- Status Non-Citizens / Linda Bosniak -- Naturalization / Liav Orgad -- Denationalization / Matthew Gibney -- Citizenship in Immigration States / Christian Joppke -- Citizenship and State Transition / Oxana Shevel -- Citizenship in Non-Western Contexts / Erin Chung -- Re-Scaling the Geography of Citizenship / Alexander Diener -- Indigenous Citizenship in Settler States / Kirsty Gover -- Secular and Religious Citizenship / Bryan S. Turner -- Performative Citizenship / Engin Isin -- Does Citizenship Matter? / Irene Bloemraad -- The Place of Territory in Citizenship / Neil Walker -- Diasporas and Transnational Citizenship / Michael Collyer -- Fragmentation of Citizenship Governance / Joel Trachtman -- Multiple Citizenship / Peter Spiro -- Multilevel Citizenship / Willem Maas -- Supranational Citizenship / Fancesca Strumia -- Political Membership and Democratic Boundaries / t Liberal and Republican Conceptions of Citizenship / Patrick Honohan -- Citizenship and Nationhood / Chaim Gans -- The History of Racialized Citizenship / David FitzGerald -- Feminist, Sexual and Queer Citizenship / Leti Volpp -- Postcolonial Citizenship / Kamal Sadiq -- Economic Theories of Citizenship Ascension / Don DeVoretz, Nahikari Irastorza.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on September 1, 2017).
Keywords: Citizenship